Efektivitas E-Book Fisika SMA/MA Terintegrasi Materi Gempa Bumi Berbasis Research Based Learning Untuk Meningkatkan Sikap Siapsiaga Peserta Didik - Nyswatul Khair; Ahmad Fauzi (JURNAL EKSAKTA PENDIDIKAN (JEP), 2022)
It is very important to develop an integrated physics e-book for earthquake disaster materials based on research based learning. This is because earthquakes are one of the most common disasters in Indonesia. Earthquake is one of the disasters that cannot be predicted when, where and the magnitude of the earthquake. One of the causes of the large number of victims due to the earthquake is the lack of knowledge and understanding of the community towards disasters so that there is a lack of preparedness in anticipating disasters early. One solution to overcome this problem is by providing earthquake material in schools using physics e-books. The purpose of this study is to determine the effectiveness of an integrated high school/MA physics e-book on earthquake material with a research-based learning model to improve students' preparedness. The research method used in this research is quasi-experimental. The research design used is a one group pretest-posttest design. In this design, one sample class is given a pretest and after being treated, a test is given as a description of the competence of students after being given a physics e-book. Based on the results of the research that has been carried out, it is concluded that the physics e-book is integrated with the earthquake material with a research based learning model that is effective in increasing the competence of students' attitudes, knowledge and skills.